Plan de acción para mitigar los riesgos ocasionados por inundación en el sector del puente de la vereda la Trinidad - Duitama (2022)
This research project aims to formulate an action plan to mitigate the effects generate floods in the community of the bridge area of the TrinidadDuitama d by village, therefore, based on information collected from the databases of lDEAM, IGAC and UNGRD, we proceeded to delimit and georeference the study area, conducting an analysis of clima affect flooding processes such as precipitatio tological variables that n, flow and temperature based on this; A flood model was made using ArcGIS and HECRAS software, delimiting the affected area, and surveys were applied to the community to determine the event of a flood. This showed th degree of knowledge and action in the at no flood study has been carried out in the area and the necessary planning to avoid construction within the river's area of influence. Therefore, an action plan was proposed as a sta community. rting point to mitigate the identified damages and guarantee the safety